Major adverse events and atrial tachycardia in Ebstein’s anomaly predicted by cardiovascular magnetic resonance - Rydman, Riikka (Heart, 2018)
OBJECTIVES: Patients with Ebstein’s anomaly of the tricuspid valve (EA) are at risk of tachyarrhythmia, congestive heart failure and sudden cardiac death. We sought to determine the value of cardiovascular magnetic resonance (CMR) for predicting these outcomes. METHODS: Seventy-nine consecutive adult patients (aged 37±15 years) with unrepaired EA underwent CMR and were followed prospectively for a median 3.4 (range 0.4–10.9) years for clinical outcomes, namely major adverse cardiovascular events (MACEs: sustained ventricular tachycardia/heart failure hospital admission/cardiac transplantation/death) and first-onset atrial tachyarrhythmia (AT). RESULTS: CMR-derived variables associated with MACE (n=6) were right ventricular (RV) or left ventricular (LV) ejection fraction (EF) (HR 2.06, 95% CI 1.168 to 3.623, p=0.012 and HR 2.35, 95% CI 1.348 to 4.082, p=0.003, respectively), LV stroke volume index (HR 2.82, 95% CI 1.212 to 7.092, p=0.028) and cardiac index (HR 1.71, 95% CI 1.002 to 1.366, p=0.037); all remained significant when tested solely for mortality. History of AT (HR 11.16, 95% CI 1.30 to 95.81, p=0.028) and New York Heart Association class >2 (HR 7.66, 95% CI 1.54 to 38.20, p=0.013) were also associated with MACE; AT preceded all but one MACE, suggesting its potential role as an early marker of adverse outcome (p=0.011). CMR variables associated with first-onset AT (n=17; 21.5%) included RVEF (HR 1.55, 95% CI 1.103 to 2.160, p=0.011), total R/L volume index (HR 1.18, 95% CI 1.06 to 1.32, p=0.002), RV/LV end diastolic volume ratio (HR 1.55, 95% CI 1.14 to 2.10, p=0.005) and apical septal leaflet displacement/total LV septal length (HR 1.03, 95% CI 1.00 to 1.07, p=0.041); the latter two combined enhanced risk prediction (HR 6.12, 95% CI 1.67 to 22.56, p=0.007). CONCLUSION: CMR-derived indices carry prognostic information regarding MACE and first-onset AT among adults with unrepaired EA. CMR may be included in the periodic surveillance of these patients.